A simulation model fusing space and agent for indoor dynamic fire evacuation analysis. (March 2016) - Niu, Lei; Song, Yiquan
Research on indoor fire emergency evacuations is crucial for hazard mitigation purposes, and dynamic indoor environments examined in this field demand a flexible solution. Current approaches separately address spatial and human elements of evacuations, producing superficial evacuation analysis results. In this paper, we employ a hierarchical structure to efficiently organize indoor accessible space and combine it with agents to simulate the indoor evacuation process. Thus, analysis functions from both accessible space and agent perspectives may be fused to thoroughly investigate simulation results. The experiment shows that this simulation model can be used to efficiently analyze evacuation characteristics of buildings for fire emergencies.